Differential pattern of mineralo -physiological attributes in indigenous cows during pre-partum vaginal prolapse (Indian Journal of Animal Production and Management, 2024)
The present study was performed to observe the differential patterns in mineralo -physiological attributes  of Sahiwal and Hariana cows during their pre-partum vaginal prolapse. During the experimental period of  five months, a total of five Sahiwal and no Hariana cows were found to be suffering from pre-partum vaginal  prolapse. The physiological and mineral attributes of prolapsed Sahiwal cows were compared with those  of healthy Sahiwal and Hariana cows. In present study, plasma concentration of calcium and phosphorus  in Sahiwal cows (6.10±0.64, 3.90±0.37 mg/dl, respectively) was found to be significantly (p
Keywords: Hariana cows; Minerals; Prolapse; Sahiwal cows